Sifabella Boardgame: Inovasi Mengupas Stigma Intoleransi Guna Merekonstruksi Hegemoni Moderasi Beragama - Zayusman, Ari; Rivauzi, Ahmad (An-Nuha, 2024)
This research is based on the phenomenon of intolerant attitudes that occur at the high school level in Padang City. The aim of this research is to provide an overview of the indications of the stigma of intolerance that occurs at the high school level in Padang City through the media of Sifabella Boardgames and to find the right way to minimize the stigma of intolerance through religious moderation. The population in this research is SMA Don Bosco, SMAN 10 Padang, SMKN 2 Padang, and MAN 2 Padang. The method used is a mix-method with a concurrent embedded model. This method combines explorative qualitative and quasi-experimental quantitative methods. Research data was obtained through interviews and direct observation as primary data and through pretest-posttest questionnaires as secondary data. Primary data is analyzed through data reduction, data presentation, and verification. Meanwhile, secondary data was processed using the paired sample T-test. The results of the research showed that 15% of research subjects were not assertive in dealing with problems, 22% of research subjects tended to be self-centered, 30% of research subjects misperceived other religions, and 18% of research subjects still did not understand self-awareness and the importance of self-reflection. The results of the paired sample T-test show that there is a significant influence on the differences in treatment given with a sign value (2-tailed) < 0.05.